THE INFLUENCE OF CREDIT RISK AND LIQUIDITY RISK ON PERFORMANCE OF SHARIA COMMERCIAL BANKS IN 2010-2015 - Ade Dian Masrur; Estu Widarwati; Deden Ramdan (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2019)
This study aims to examine the effect of credit risk and liquidity risk to commercial islamic bank performance. Credit risk is proxied by NPF, and liquidity risk is proxied by FDR while performance is proxied by ROA, in addition this research use control variable, there are Size and Leverage. The data in this study obtaine from the Company's Financial Statements Banking Publications from each company’s website. Based on saturate sampling method, the sample is 12 of commercial islamic bank in Indonesia periode 2010-2015, observation unit total is 66 (unbalanced panel) . The type of data is secondary data, which is a combination of time series and cross section data. The methodology is the Generalized Least Square (GLS) panel data analysis with FEM model, use annual data from twelve Islamic banks, which listed in Otoritas Jasa Keuangan (OJK) for the periode 2010-2015 and use statistic tool Eviews 8. The results shows that the variable NPF as credit risk’s proxy is significant negative effect on ROA, and FDR as liquidity risk’s proxy is significant positive effect on ROA. The results of the use variable control shows bank heterogenity, there are size and leverage effect to performance. Coefficient of determination, which shows the magnitude of the influence NPF and FDR, and two control variable, there are Size and Leverage to ROA are 53.56%, while the rest of 46.44% explained by other causes outside the model.